An On-line Computer System for a Rehabilitation Hospital - Vallbona, C.; Spencer, W. A.; Levy, A. H.; Baker, R. L.; Liss, D. M.; Pope, S. B. (Methods of Information in Medicine, 1968)
An on-line computer system has been implemented for processing medical information at the Texas Institute for Rehabilitation and Research. The major objectives of the system are: 1. to improve the process of patient care by expediting the flow of information among, members, of .the rehabilitation team, 2. to facilitate the utilization of medical data for research purposes, 3. to enhance efficient hospital management, and 4. to obtain accurate data for an effective study of. the cost of hospitalization.The system consists of the following interrelated programs: a) recording- of physiological monitoring, b) on-line processing of data collected at the bedside, c) processing of laboratory data, d) on-line processing of results of physiological studies, e) processing of data pertaining to treatments administered to patients, f) on-line calculation of fluid and electrolyte requirements, and g) statistical analysis of the hospital census.The on-line computer facility is based on a time-shared teleprocessing system located at Baylor University College of Medicine and time-shared with various departments of the College. Remote terminal units installed at the Texas Institute for Rehabilitation and Research are connected by cable with the computer at the College of Medicine.Im Texas Institute for Rehabilitation and Research wurde ein On-line-Computer-System für die Verarbeitung medizinischer Daten entwickelt. Die wesentlichsten Ziele dieses Systems sind: 1. Die Verbesserung der Pflege des Patienten durch Beschleunigung des Informationsflusses zwischen den Mitgliedern des Rehabilitatiohsteams, 2. die Erleichterung der Nutzbarkeit der medizinischen Daten für Forschungszwecke, 3. die Erhöhung der Leistungsfähigkeit der Klinikverwaltung und 4. die Gewinnung exakter Unterlagen für eine Untersuchung der Kosten der Hospitalisierung.Das System besteht aus den folgenden, untereinander verbundenen Programmen: a) Registrierung der laufenden Überwachung der physiologischen Funktionen, b) On-line-Verarbeitung der am Krankenbett gesammelten Daten, c) Verarbeitung der Laboratoriumsdaten, d) On-line-Verarbeitung der Ergebnisse physiologischer Untersuchungen, e) Aufbereitung der Daten, die sich auf die Behandlung des Patienten beziehen, f) On-line-Berechnungen des Bedarfs an Flüssigkeit und Elektrolyten und g) Analyse der statistischen Erhebungen des Krankenhauses.Die On-line-Computer-Anlage basiert auf dem Simultanzeit-Fernverarbeitungs-System des Baylor University College of Medicine, das mit verschiedenen anderen Abteilungen des College geteilt wird. Die peripheren Anschlußgeräte des Texas Institute for Rehabilitation and Research sind durch Kabel mit dem Computer des College of Medicine verbunden.